2014
DOI: 10.1007/s00018-014-1621-4
|View full text |Cite
|
Sign up to set email alerts
|

A complex signaling network involving protein kinase CK2 is required for hepatitis C virus core protein-mediated modulation of the iron-regulatory hepcidin gene expression

Abstract: Hepatitis C virus (HCV) infection is associated with hepatic iron overload and elevated serum iron that correlate to poor antiviral responses. Hepcidin (HAMP), a 25-aa cysteine-rich liver-specific peptide, controls iron homeostasis. Its expression is up-regulated in inflammation and iron excess. HCV-mediated hepcidin regulation remains controversial. Chronic HCV patients possess relatively low hepcidin levels; however, elevated HAMP mRNA has been reported in HCV core transgenic mice and HCV replicon-expressing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 96 publications
3
21
0
Order By: Relevance
“…We have previously showed that HCV core induces HAMP gene expression in hepatoma cells 23 and this may also apply to early HCV infection. Conversely, upon established infection, hepcidin expression dropped in our in vitro model and in patient sera, 12,13 in step with studies from chronic HCV patients with low intrahepatic HAMP mRNA 24 and decreased serum hepcidin, 12,13 and earlier in vitro RNA data.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…We have previously showed that HCV core induces HAMP gene expression in hepatoma cells 23 and this may also apply to early HCV infection. Conversely, upon established infection, hepcidin expression dropped in our in vitro model and in patient sera, 12,13 in step with studies from chronic HCV patients with low intrahepatic HAMP mRNA 24 and decreased serum hepcidin, 12,13 and earlier in vitro RNA data.…”
Section: Discussionmentioning
confidence: 91%
“…Then, the RNA fraction was subjected to qRT-PCR, essentially as described in ref. 23 The gene specific primers used for HAMP, 18S rRNA, IL-6 and NS3-2A have been published elsewhere. 23,59 Results were analyzed with the internal standard-curve method and normalized to 18S rRNA to provide the relative mRNA expression.…”
Section: Mrna and Protein Expression Analysesmentioning
confidence: 99%
See 3 more Smart Citations